АНАЛІЗ ПРОБЛЕМИ ГОТОВНОСТІ ДО ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ МАЙБУТНІХ ТЕХНІКІВ ГАЛУЗІ ЗВ'ЯЗКУ В ПСИХОЛОГІЧНІЙ, ПЕДАГОГІЧНІЙ І МЕТОДИЧНІЙ ЛІТЕРАТУРІ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2010)
This article has the definition of term «Activity» analyzed. The essence of scientific and working activities is exposed. Also, criterias of definition of readiness for professional activity were formulated